2013
DOI: 10.2478/rehab-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between body posture and postural stability of school children

Abstract: StreszczenieWstęp: Mała aktywność ruchowa, częste przebywanie w pozycji siedzącej i obciążenia szkolne sprawiają, że wady postawy ciała stały się zjawiskiem powszechnym.Cel pracy. Głównym celem pracy jest określenie czy istnieje związek między równowa-gą ciała, a wadami postawy w obrębie tułowia u dzieci w wieku wczesnoszkolnym.Materiał i metody: Do badań włączono 104 uczniów: 46 chłopców i 58 dziewczynek w klasach I -III. Do oceny postawy ciała wykorzystano System Zebris z oprogramowaniem WinSpine 2.3, a do o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…This may be due to the lack of adequately developed sensory integration capabilities (especially in the processing of vestibular and visual experiences). This process is still developing in children [21]. our study also revealed that 7-8-year-olds had quite a hard time balancing their bodies.…”
Section: Discussionsupporting
confidence: 57%
“…This may be due to the lack of adequately developed sensory integration capabilities (especially in the processing of vestibular and visual experiences). This process is still developing in children [21]. our study also revealed that 7-8-year-olds had quite a hard time balancing their bodies.…”
Section: Discussionsupporting
confidence: 57%
“…It has been proven that patients with idiopathic scoliosis have poorer posture stability control compared to healthy individuals, and left-sided scoliosis leads to poorer stabilometric parameters in children [26,27]. In the study by Walicka-Cupryś et al, it has been established that increased posterior torso tilt and increased anterior pelvic tilt result in an abnormal load on the anterior parts of the feet, the left feet in particular, and poorer stabilometric parameters including sagittal-plane deviation [28]. In our study, we assumed increased lumbar lordosis and thoracic kyphosis to be the exclusion criteria, to eliminate the influence of those factors on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Partly similar results were reported by Walicka-Cupryś et al . These authors examined children with genu valgum and found that the defect was most common in overweight children (28.6%), followed by children with normal weight (14.7%), and it was least frequent in underweight subjects (10.7 %) 25…”
Section: Discussionmentioning
confidence: 99%
“…These define points with reference to which the device specifies the positions of pointer markers. By applying the pointer to the characteristic anatomical locations on the body and by activating the device it is possible to visualise the relevant points on the screen and to create a three-dimensional image of the body posture 25 26…”
Section: Introductionmentioning
confidence: 99%